Targeting cancer stem cells with defined compounds and drugs - Naujokat, Cord; Laufer, Stefan (Journal of Cancer Research Updates, 2013)
Cancer stem cells (CSCs) are a subpopulation of tumor cells that possess self-renewal and tumor initiation capacity and the ability to give rise to the heterogenous lineages of cancer cells that comprise the tumor. CSCs possess numerous intrinsic mechanisms of resistance to chemotherapeutic drugs, novel tumor-targeted drugs and radiation therapy, allowing them to survive current cancer therapies and to initiate tumor recurrence and metastasis. Recently, different pathways that confer resistance and survival of CSCs, but also compounds and drugs that selectively target some of these pathways in CSCs have been identified. Such compounds and drugs include antibiotics like salinomycin, phytochemicals such as parthenolide, cyclopamine, EGCG, resveratrol, curcumin, sulforaphane and oxymatrine, the small molecule inhibitors vismodegib and repertaxin, monoclonal antibodies and antibody constructs raised against cell surface proteins expressed by CSCs, and, surprisingly, some classical drugs such as metformin, tranilast and thioridazine. These agents exhibit significant anti-CSC activity, alone or in combination with cytostatic drugs or tumor-targeted drugs, as recently shown in vitro and in human xenograft mice. Since current cancer therapies fail to eliminate CSCs, leading to cancer recurrence and progression, selective targeting of CSCs with compounds and drugs introduced herein may represent a novel therapeutic strategy to eradicate cancer.